Perancangan Sistem Pendukung Keputusan Penerimaan Bantuan Nelayan dan Pembudidaya Menggunakan Metode AHP - Tri Andika Buheli; Dian Novian; Manda Rohandi (Gorontalo State University, 2021)
Every govermment agency certainly has a program in the form of providing assistance to the community and must be given to recipients who are worthy and deserve it. There are several problems in determing recipients of assistance, such as it is not well distributed and well targeted to the recipinets. In addition, the manual data collection process often goes wrong and there are no determined citeria for potential recipinets for assistance. This study aims to apply the AHP (Analytical Hierarchy Process) ad decision support in providing assistance to firherman and cultivators. The system built is capable and feasible to be used for determining the provision of assistance to fisherman and cultivators. This system is able to be a solution in solving problems regarding determination of receipt of assistance to fisherman and cultivators to be more tell targeted because it is based on priorities with the determined criteria. Keywords : Assistance, Decision Support System, AHP (Analytical Hierarchy Process)